(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1993)
Three new species of benthic Foraminifera are here described from the Lower Aptian limestones of the Murge Region (Apulia, Southern Italy). The identified species are: Pseudolituonella conica sp. n., Voloshinoides murgensis sp. n., Archaeosepta coratina sp. n.